1973
DOI: 10.1901/jeab.1973.19-65
|View full text |Cite
|
Sign up to set email alerts
|

The Maintenance of Key Pecking by Stimulus‐contingent and Response‐independent Food Presentation

Abstract: Three naive pigeons were exposed to a series of two-component multiple schedules of response-independent food presentation. The component schedules were sometimes identical (non-differential procedures) and sometimes different (differential procedures). High rates of key pecking were nmaintained in all the differential procedures, and pecking decreased substantially in non-differential procedures, even when the frequency of food presentation in non-differential procedures was higher than in differential proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
144
2

Year Published

1977
1977
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(161 citation statements)
references
References 19 publications
(39 reference statements)
15
144
2
Order By: Relevance
“…Finally, even in cases in which behavioral contrast did occur in S-/S-components, the absolute response rates associated with these components may have been so low that relatively large increases went unnoticed. Whatever the case, the observation that S-/S-responding may show positive behavioral contrast has implications for several interpretations of behavioral contrast, such as "relative reinforcement theory" (Reynolds, 1961b), "additivity theory" (Gamzu & Schwartz, 1973;Schwartz & Gamzu, 1977),and "behavioral competition theory" (Hinson & Staddon, 1978). Reynolds (1961 b) suggested that positive behavioral contrast results from an increase in the relative reinforcement frequency associated with the stimulus showing contrast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, even in cases in which behavioral contrast did occur in S-/S-components, the absolute response rates associated with these components may have been so low that relatively large increases went unnoticed. Whatever the case, the observation that S-/S-responding may show positive behavioral contrast has implications for several interpretations of behavioral contrast, such as "relative reinforcement theory" (Reynolds, 1961b), "additivity theory" (Gamzu & Schwartz, 1973;Schwartz & Gamzu, 1977),and "behavioral competition theory" (Hinson & Staddon, 1978). Reynolds (1961 b) suggested that positive behavioral contrast results from an increase in the relative reinforcement frequency associated with the stimulus showing contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Additivity theory (Gamzu & Schwartz, 1973;Schwartz & Gamzu, 1977) also has troubles accounting for positive behavioral contrast in S-/S-responding. According to additivity theory, autopecks are elicited by the presentation of a stimulus when that stimulus is "differentially associated with a higher frequency of food presentations than obtains in the absence of that stimulus" (Gamzu & Schwartz, 1973, p. 70).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Gamzu and Schwartz (1973) suggested that response rate to a stimulus is determined by two additive factors-first, the operant contingency of reinforcement associated with responding and, second, the Pavlovian relation of the stimulus to reinforcement. According to Gamzu and Schwartz, it is the Pavlovian relation that is affected by the introduction of the poorer schedule and that produces contrast.…”
Section: Functional Properties Of the Successive And Simultaneous Dismentioning
confidence: 99%
“…They pecked at a lower rate during the stimulus that signaled the lower rate of food (the less favorable stimulus). And they pecked both stimuli at a lower rate when the stimuli signaled equal rates of food presentation.Several recent, additive, theories have related these responses to the behavioral contrast which occurs when pigeons respond on multiple variable-interval variable-interval (mult VI VI) schedules of reinforcement (e.g., Gamzu & Schwartz, 1973; Hearst & Jenkins, 1974;Rachlin, 1973). Mult VI VI schedules are similar to mult VT VT schedules, except that food is not given freely.…”
mentioning
confidence: 99%
“…Several recent, additive, theories have related these responses to the behavioral contrast which occurs when pigeons respond on multiple variable-interval variable-interval (mult VI VI) schedules of reinforcement (e.g., Gamzu & Schwartz, 1973; Hearst & Jenkins, 1974;Rachlin, 1973). Mult VI VI schedules are similar to mult VT VT schedules, except that food is not given freely.…”
mentioning
confidence: 99%